The Success of Pure Event's Collaboration with Sari Roti as Sponsor for Jar of Memories Interpersonal Communication Perspective - Lubis, Jasmine Fajira; Deni, Indira Fatra (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Abstrak Tujuan dari penelitian ini adalah untuk mengkaji peran komunikasi interpersonal dalam keberhasilan kerja sama antara peristiwa murni dan sarity ketika serangkaian ingatan terjadi. Penelitian ini menggunakan metode kualitatif dengan pendekatan wawancara semi terstruktur untuk memahami dinamika komunikasi secara kolaboratif. Lokasi penelitian tersebut terletak di PT. Nippon Indosari Corpindo Tbk, Medan Sumatera Utara. Data dikumpulkan murni melalui wawancara dengan acara, sebagai informasi dari pelanggan dan literatur, sebagai informasi dari pelanggan dan literatur. Teknik perekaman data meliputi wawancara, observasi langsung, dan dokumentasi. Analisis data dilakukan dengan menggunakan mileage dan model Hooverman menggunakan teknik triangulasi untuk memastikan validitas hasil. Hasil penelitian menunjukkan bahwa komunikasi interpersonal yang efektif meningkatkan koordinasi, profesionalisme, dan keberhasilan acara. Dampak dari penelitian ini menyoroti pentingnya transparansi dan evaluasi rutin dalam menjaga kemitraan jangka panjang antara penyelenggara dan sponsor untuk keberlanjutan kerja sama di masa depan. Kata Kunci: Komunikasi Interpersonal, Kerja Sama, Event Organizer, Sponsorship, Evaluasi. Abstract The purpose of this study is to examine the role of interpersonal communication in the success of cooperation between pure and sarity events when a series of memories occur. This study uses a qualitative method with a semi-structured interview approach to understand the dynamics of communication collaboratively. The location of the study is located at the PT. Nippon Indosari Corpindo Tbk, Medan North Sumatra. Data were collected purely through interviews with events, as information from customers and literature, as information from customers and literature. Data recording techniques include interviews, direct observation, and documentation. Data analysis was carried out using the mileage and Hooverman models using triangulation techniques to ensure the validity of the results. The results of the study indicate that effective interpersonal communication improves coordination, professionalism, and event success. The impact of this study highlights the importance of transparency and regular evaluation in maintaining long-term partnerships between organizers and sponsors for the sustainability of future cooperation. Keywords: Interpersonal communication, cooperation, Event Organizer, sponsorship, evaluation.